To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 6x^2+ax+bx-10. To find a and b, set up a system to be solved.

You are watching: 6x^2-11x-10=0

Since ab is negative, a and b have the opposite signs. Since a+b is positive, the positive number has greater absolute value than the negative. List all such integer pairs that give product -60. 6x2+11x-10=0 Two solutions were found : x = -5/2 = -2.500 x = 2/3 = 0.667 Step by step solution : Step 1 :Equation at the end of step 1 : ((2•3x2) + 11x) - 10 = 0 Step 2 :Trying come ...
6x2+11x-140=0 Two solutions were found : x = -35/6 = -5.833 x = 4 Step by step solution : Step 1 :Equation at the end of step 1 : ((2•3x2) + 11x) - 140 = 0 Step 2 :Trying to factor through ...
How do you find the number of complex, real and rational roots of displaystyle3x^2+11x-10=0 ?
https://socratic.org/questions/how-do-you-find-the-number-of-complex-real-and-rational-roots-of-3x-2-11x-10-0
The two roots are real, but not rational given by x= displaystylefrac-11pmsqrt2416 . No complex roots.Explanation:This is a quadratic expression. Quadratic formula can be used ...
8x2+11x-10=0 Two solutions were found : x = -2 x = 5/8 = 0.625 Step by step solution : Step 1 :Equation at the end of step 1 : (23x2 + 11x) - 10 = 0 Step 2 :Trying to factor by ...
x2+11x-210=0 Two solutions were found : x = 10 x = -21 Step by step solution : Step 1 :Trying to factor by splitting the middle term 1.1 Factoring x2+11x-210 The first term is, x2 ...
6x2-11x-10=0 Two solutions were found : x = -2/3 = -0.667 x = 5/2 = 2.500 Step by step solution : Step 1 :Equation at the end of step 1 : ((2•3x2) - 11x) - 10 = 0 Step 2 :Trying to ...
More Items     To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 6x^2+ax+bx-10. To find a and b, set up a system to be solved.
Since ab is negative, a and b have the opposite signs. Since a+b is positive, the positive number has greater absolute value than the negative. List all such integer pairs that give product -60.
All equations of the form ax^2+bx+c=0 can be solved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
This equation is in standard form: ax^2+bx+c=0. Substitute 6 for a, 11 for b, and -10 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^2+bx=c.

See more: How To Say Hurry Up In Korean ? "Hurry Up!" How To Say Hurry Up In Korean

Divide frac116, the coefficient of the x term, by 2 to get frac1112. Then add the square of frac1112 to both sides of the equation. This step makes the left hand side of the equation a perfect square.  